Method and Device for Speed Change by the Epicyclic Gear Train with Stepped-Planet Gear Set - Malashchenko Volodymyr (Research Works of Air Force Institute of Technology, 2016)
The article describes new method and device for continuously variable speed change management via compound epicyclic gearing with composite planet gears and closed circuit hydrosystem, when the speed control element is either outer ring gear (annulus) or the carrier or sun gear. In each case, the control element connected to closed circuit hydrosystem and can be in motion or immovable depending on the bandwidth of hydrosystem’s regulating throttle. We had held theoretical research and received graphic dependences between velocities of driving, control and driven elements by means of computer programing.